Assessment of Bearing Dynamic Characteristics by Numerical Modeling with Effects of Oil Film and Centrifugal Deformation. (6th November 2018) - Yu, Jie; Yuan, Wei; Li, Songsheng; Yao, Wenbing
Abstract : This paper developed a modified quasi-static model (MQSM), considering the oil film thickness between the bearing parts and the centrifugal deformation of the inner ring, and contrasting with traditional quasi-static model (TQSM), to analyze the dynamic characteristics of spindle bearing. The model was verified with the experimental results. A systematic parametric analysis was made to investigate the influence of applied load, inner ring rotation speed ( ni ), and the radius coefficient of groove curvature (RCR) on the contact load, contact angle, and heat generating rate. The results show that there is a smaller influence on the contact load, contact angle, and heat generation of bearing with the changes of ni and axial load (F a ) of bearing in the case of MQSM and TQSM. But the radial load (F r ) and RCR have great influence on this.